Changes in Prostaglandin-associated Periorbital Syndrome After Switch from Conventional Prostaglandin F2α Treatment to Omidenepag Isopropyl in 11 Consecutive Patients. Issue 4 (April 2020) - Nakakura, Shunsuke; Terao, Etusko; Fujisawa, Yasuko; Tabuchi, Hitoshi; Kiuchi, Yoshiaki
Abstract : Purpose: We evaluated the recovery of patients with PAPS for whom the treatment regimen switched from conventional prostaglandin F2α analogues to a new selective prostaglandin-EP2 agonist: omidenepag isopropyl. Patients and Methods: From November 2018 to July 2019, we prospectively evaluated 11 patients who had been using conventional PGF2α drugs. Digital photographs of the patients were taken before the start of omidenepag isopropyl therapy and ~3 and 6 months after. Three independent observers used the photographs to judged recovery according to the 5 signs of PAPS: deepening of the upper eyelid sulcus (DUES), flattening of the lower eyelid bags, upper eyelid ptosis, ciliary hypertrichosis, and periorbital skin hyperpigmentation. Results: The mean age of patients was 61, and 7 patients were female. The original PGF2α drugs were bimatoprost, latanoprost, travoprost, and tafluprost. The mean duration of PGF2α treatment was 65 months. PAPS signs were evaluated in 10 patients after 3 months and in all 11 patients after 6 months: After 3 and 6 months, DUES improved in 3 and 3 patients, respectively; flattening of the lower eyelid bags improved in 1 and 2 patients, respectively; upper eyelid ptosis did not improve in any patients; ciliary hypertrichosis improved in 0 and 2 patients, respectively; and eyelid pigmentation improved in 2 and 8 patients, respectively. The 3 patients who showed improvement in DUES at 6 months had all previously used bimatoprost. Conclusions: Some PAPS signs improved after patients started taking omidenepag isopropyl. Our findings will be useful for patients taking antiglaucoma eye drops.